PENCAPAIAN KEMAMPUAN BERPIKIR KRITIS MATEMATIS SISWA PADA MATERI TRIGONOMETRI - Risah, Yayu; Sutirna, Sutirna; Hakim, Dori Lukman (IKIP Siliwangi, 2021)
In this article, we want to discuss one of the higher-order thinking skills, namely students' mathematical critical thinking on trigonometric material, related to the achievement of class X MIPA high school students. Descriptively reviewing students 'answers to questions containing indicators of mathematical critical thinking ability with a total of 35 students, was taken based on the considerations made by the researcher through purposive sampling and the students' critical thinking levels were categorized into high, medium, and low. The data collection technique uses tests of mathematical critical thinking skills and research results based on analysis by obtaining the results of achieving critical thinking skills in students seen from high category students if they meet all indicators of mathematical critical thinking skills, students in the moderate category meet 2 indicators of mathematical critical thinking skills, and Students in the low critical thinking category meet 1 indicator of mathematical critical thinking skills.